2008
DOI: 10.2353/jmoldx.2008.080018
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Molecular Characterization of Formalin-Fixed, Paraffin-Embedded Tissues by microRNA Expression Profiling

Abstract: Formalin-fixed, paraffin-embedded tissues are an invaluable tool for biomarker discovery and validation. As these archived specimens are not always compatible with modern genomic techniques such as gene expression arrays, we assessed the use of microRNA (miRNA) as an alternative means for the reliable molecular characterization of formalin-fixed, paraffin-embedded tissues. Expression profiling using two different microarray platforms and multiple mouse and human formalinfixed, paraffin-embedded tissue types re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 21 publications
(21 reference statements)
3
77
1
1
Order By: Relevance
“…A similar scenario may contribute to breast cancer development : miR-9, miR-19b, miR-146, miR-181c, miR-183, miR-200c, miR-205, miR-223, miR-423, miR-425 Y: let-7a, miR-32, miR-33b, miR-369, miR-409, miR-424, miR-431, miR-451, miR-496, miR-503 miR-516 Ratner et al (2010) EEC carcinoma versus benign tissue from control patients [: miR-34a, miR-182, miR-183, miR-200a, miR-205, miR-572, miR-622, miR-650 Y: miR-411, miR-487b Chung et al (2009) EEC versus benign tissue from control patients [: miR-10a, miR-23a, miR-25, miR-28, miR-34a, miR-95, miR-103, miR-106a, miR-107, miR-130b, miR-141, miR-151, miR-155, miR-17-5p, miR-182, miR-183, miR-184, miR-191, miR-194, miR-200a, miR-200c, miR-203, miR-205, miR-210 : miR-10a, miR-31, miR-96, miR-133b, miR-141, miR-142-5p, miR-155, miR-182, miR-200a, miR-200b, miR-200c, miR-203, miR-205, miR-210, miR-363, miR-429, miR-432, miR-449 Y: miR-99b, miR-133, miR-193a, miR-193b, miR-204, miR-368 Boren et al (2008) EEC versus atypical hyperplasia versus normal endometrium [: let-7c, miR-103, miR-106a, miR-107, miR-181a, miR-185, miR-210, miR-423 Y: let-7i, miR-30c, miR-152, miR-193, miR-221 MiRNA represents a new class of biomarkers that can complement existing conventional markers, including metabolites, antigens and mRNA transcripts. The fact that miRNAs remain largely intact in formalin-fixed, paraffinembedded clinical samples highlights their potential in molecular phenotyping of benign and malignant reproductive disorders as well as for monitoring treatment efficacy (Bitossi et al 2008, Szafranska et al 2008, Tam 2008, Jorgensen et al 2010, Nuovo 2010, Schuster et al 2010. Furthermore, recent evidence suggests that some neoplastic processes, for example, ovarian cancer, generate mRNA profiles in blood cells characteristic of the tumours, suggesting that whole blood miRNA profiling could be used for diagnostic purposes (Balch et al 2009, Lodes et al 2009, Resnick et al 2009, Hausler et al 2010.…”
Section: The Mirna-foxo Axis In Endometrial Carcinogenesismentioning
confidence: 99%
“…A similar scenario may contribute to breast cancer development : miR-9, miR-19b, miR-146, miR-181c, miR-183, miR-200c, miR-205, miR-223, miR-423, miR-425 Y: let-7a, miR-32, miR-33b, miR-369, miR-409, miR-424, miR-431, miR-451, miR-496, miR-503 miR-516 Ratner et al (2010) EEC carcinoma versus benign tissue from control patients [: miR-34a, miR-182, miR-183, miR-200a, miR-205, miR-572, miR-622, miR-650 Y: miR-411, miR-487b Chung et al (2009) EEC versus benign tissue from control patients [: miR-10a, miR-23a, miR-25, miR-28, miR-34a, miR-95, miR-103, miR-106a, miR-107, miR-130b, miR-141, miR-151, miR-155, miR-17-5p, miR-182, miR-183, miR-184, miR-191, miR-194, miR-200a, miR-200c, miR-203, miR-205, miR-210 : miR-10a, miR-31, miR-96, miR-133b, miR-141, miR-142-5p, miR-155, miR-182, miR-200a, miR-200b, miR-200c, miR-203, miR-205, miR-210, miR-363, miR-429, miR-432, miR-449 Y: miR-99b, miR-133, miR-193a, miR-193b, miR-204, miR-368 Boren et al (2008) EEC versus atypical hyperplasia versus normal endometrium [: let-7c, miR-103, miR-106a, miR-107, miR-181a, miR-185, miR-210, miR-423 Y: let-7i, miR-30c, miR-152, miR-193, miR-221 MiRNA represents a new class of biomarkers that can complement existing conventional markers, including metabolites, antigens and mRNA transcripts. The fact that miRNAs remain largely intact in formalin-fixed, paraffinembedded clinical samples highlights their potential in molecular phenotyping of benign and malignant reproductive disorders as well as for monitoring treatment efficacy (Bitossi et al 2008, Szafranska et al 2008, Tam 2008, Jorgensen et al 2010, Nuovo 2010, Schuster et al 2010. Furthermore, recent evidence suggests that some neoplastic processes, for example, ovarian cancer, generate mRNA profiles in blood cells characteristic of the tumours, suggesting that whole blood miRNA profiling could be used for diagnostic purposes (Balch et al 2009, Lodes et al 2009, Resnick et al 2009, Hausler et al 2010.…”
Section: The Mirna-foxo Axis In Endometrial Carcinogenesismentioning
confidence: 99%
“…Some, however, have noted a decrease in miRNAs detected with time in storage. This could indicate degradation of miRNA over time or a decrease in labelling efficiency due to increased recovery of short non-specific RNA (17)(18)(19). One study found a number of miRNAs to be up regulated in FFPE but not FF samples, which was hypothesised to be caused by non-specific binding of fragmented mRNA and immature miRNA to the array.…”
Section: Discussionmentioning
confidence: 99%
“…One potential miR-424 target, ITGAV, has previously been seen to significantly correlate with differentiation and metastasis in laryngeal and hypopharyngeal carcinomas (29,32). A number of studies investigating the usefulness of miRNA expression analysis in FFPE tissue have been performed, and many show good correlation between FFPE and FF samples (16)(17)(18). Some, however, have noted a decrease in miRNAs detected with time in storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus here was exclusively on miRNA expression, since miRNAs are strongly implicated in the pathogenesis of numerous malignancies and deregulated expression both in epithelial and cancer associated stromal cells have important consequences in CRC 2,3,5 . Moreover miRNAs are stable to extraction and analysis from conventional archival formalin-fixed paraffin-embedded tissue, making them powerful biomarkers for diagnosis and prognostication on human tissue subjected to conventional processing in routine histopathological laboratories 9,10 . However, our methodology could very easily be adapted for genomic and proteomic analysis, further emphasizing the versatility of this approach.…”
Section: Discussionmentioning
confidence: 99%